Okoljevarstveno navskrižje! habitatov ranljivih vrst ptic in električnega daljnovodnega omrežja - Razpotnik Visković, Nika (Geografski vestnik, 2007)
Power-line infrastructure affects birds directly and indirectly, in positive and negative way. The most concerning are threats of collisions with wires and electrocutions on power poles, but they can be minimized by considering both technical and ornithological factors in the planning and maintenance process. The paper presents a model which can be used for identifying the most dangerous power-line corridors and it proposes step-by-step strategy for eliminating the threats of electrocutions of eagle owls Bubo bubo in western part of Slovenia.
Keywords: bird; ptice; habitati; električno omrežje; daljnovodi; environmental protection; varstvo narave; Slovenia; Slovenija